Relationships between dry-land resistance training and swim start performance and effects of such training on the swim start: A systematic review - Thng, S.; Pearson, S.; Keogh, J. W. L. (Sports Medicine, 2019)
Background: The swim start requires an explosive muscular response of the lower body musculature to effectively initiate movement off the starting blocks. There are currently key gaps in the literature evaluating the relationship between dry-land resistance training and swim start performance and the effects of this training on swim start performance, as assessed by the time to 5, 10 or 15 m. Objectives: The aims of this systematic review were to critically appraise the current literature on (1) the acute relationship between dry-land resistance training and swim start performance and (2) the acute and chronic effects of dry-land resistance training on swim start performance. Methods: An electronic search using AusportMed, Embase, Medline (Ovid), SPORTDiscus and Web of Science was performed. The methodological quality of the studies was evaluated using the Newcastle-Ottawa quality assessment scale (NOS) (cross-sectional studies) and the Physiotherapy Evidence Database (PEDro) scale (intervention studies). Results: Sixteen studies met the eligibility criteria, although the majority did not utilise the starting blocks or technique currently used in elite swimming. Swim start performance was near perfectly related (r > 0.90) to vertical bodyweight jumps and jump height. Post-activation potentiation and plyometrics were found to produce significant improvements in acute and chronic swim start performance, respectively. Conclusion: While there appears to be strong evidence supporting the use of plyometric exercises such as vertical jumps for monitoring and improving swim start performance, future studies need to replicate these findings using current starting blocks and techniques and compare the chronic effects of a variety of resistance training programmes.